Beaver wetland and lake effects on Francisella tularensis in Swedish landscapes and hares - Pihlgren Hökby, Lovisa (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2022)
The zoonotic disease tularemia is caused by the bacterium Francisella tularensis that infects both humans and wildlife in Sweden. Associations between outbreaks of tularemia and lakes and rivers have earlier been observed, and semi-aquatic rodents and mosquitoes are believed to be key species groups in the epidemiological cycle of the disease. I have conducted a series of landscape analyses to assess land cover properties with focus on water availability at different spatial scales in areas of tularemia incidence, using data on hares found dead (n= 452) with known tularemia status, collected in 2016-2021, and land cover properties. As a complement, 56 water samples (biofilm and surface water) from lakes and beaver ponds in Sweden, covering latitudes from N 59° 29.0582’ in the south, to N 65° 52.4261’ in the north, were collected to investigate the occurrence of tularemia in different freshwater ecosystems. Results show significant correlations between tularemia occurrence and high soil moisture, and local proportion of inland water area. Water proximity as well as proportional wetland area both lack significant effects on tularemia status in hares. In water samples, I found F. tularensis in 11% of 56 samples, which were all taken from beaver systems. No difference in sampling depth could be found as F. tularensis was found in both biofilm and surface water. I suggest further investigations on F. tularensis in wetlands to a) assess the role of water biogeochemistry including pH, turbidity, and nutrient levels for occurrence and environmental persistence of the bacterium and b) evaluate the role of beaver systems for the epizootiology and epidemiology of tularemia with beavers as either reservoirs and/or beaver systems favoring vector (mosquito) habitat.